1995
DOI: 10.1063/1.359848
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation spectroscopy applied to porous silicon films

Abstract: A monoenergetic slow positron beam has been used for the first time to profile porous silicon films. High values of the Doppler-broadened line shape parameters are observed, which correspond to positron annihilation within the porous layers and these are attributed to the decay of para-positronium. After allowing for the reduced density of the porous film, fitted values of thickness were deduced which were in reasonable agreement with values obtained from ellipsometry measurements. Low values of the Doppler pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…For samples a, b and c the positrons probe only the TiN film itself and have no interaction with the Si substrate. In the cases of the thinner samples d, e and f, however, a steady increase in the value of S at incident energies above 15 keV is consistent with positrons annihilating in the Si which is known to have a value of 0.493 in this experimental system [14]. This conclusion is confirmed by the estimated values of film thickness given in table 1.…”
Section: Discussionsupporting
confidence: 74%
“…For samples a, b and c the positrons probe only the TiN film itself and have no interaction with the Si substrate. In the cases of the thinner samples d, e and f, however, a steady increase in the value of S at incident energies above 15 keV is consistent with positrons annihilating in the Si which is known to have a value of 0.493 in this experimental system [14]. This conclusion is confirmed by the estimated values of film thickness given in table 1.…”
Section: Discussionsupporting
confidence: 74%
“…Others [11][12][13] have observed a very long positron lifetime ͑up to 20 ns͒ indicative of positronium formation in the pores. Most recently, Knight et al, 14 through investigations with a slow positron beam, again found evidence of positronium formation within the porous layer. These investigations show that positrons are sensitive to the near-surface, and surface of porous silicon, and that formation of positronium occurs.…”
Section: Introductionmentioning
confidence: 94%
“…A rise in S implies a narrowing of the line. Such narrowing occurs when for instance vacancies [40], large open volume defects (voids) [41,42] or pores are present in a sample [43].…”
Section: Doppler Broadeningmentioning
confidence: 99%